A Max Lucado Children's Treasury : A Child's First Collection - Lucado, Max (Nashville, TN : Thomas Nelson, 2007)
Offers hope and encouragement to parents and children alike in a collection of stories, including "The Crippled Lamb," "Jacob's Gift," "Just in Case You Ever Wonder," and "The Way Home: A Princess Story."
Just in case you ever wonder -- The crippled lamb -- The way home -- Jacob's gift.
First work originally published: Dallas : Word Pub., 1992. 2nd work originally published: Dallas : Word Pub., 1994. 3rd work originally published: 2005. 4th work originally published: 1998.
Keywords: Christian life -- Fiction; Short stories